Diagnostic value of the cerebrospinal fluid lipoarabinomannan assay for tuberculous meningitis: a systematic review and meta-analysis - Chen, Ya-Li; Zhu, Meng-Meng; Guan, Cui-Ping; Zhang, Yan-An; Wang, Mao-Shui (Frontiers in Public Health, 2023)
Objective: This systematic review aims to evaluate the diagnostic accuracy of cerebrospinal fluid (CSF) lipoarabinomannan (LAM) assays in detecting tuberculous meningitis (TBM). Methods: A systematic review search was conducted in PubMed and five other databases up to April 2023. Studies, which evaluated the diagnostic accuracy of CSF LAM assays, were included, with definitive or composite reference standard as reference standards. The quality of the included studies was assessed using the QUADAS-2 tool. We performed bivariate random-effects meta-analysis, and calculated the summary diagnostic statistics. Results: A total of six studies, including a sample size of 999, were included in the final analysis. The pooled sensitivity, specificity, and area under the receiver operating characteristic curve (AUC) of CSF LAM for diagnosing TBM were determined as 0.44 (95% CI: 0.31-0.58), 0.89 (95% CI: 0.81-0.93), and 0.76 (95% CI: 0.73-0.80), respectively. Significant heterogeneity was observed in both sensitivity (Q=73.82, p<0.01; I2=86.45, 95%CI: 79.64-93.27) and specificity (Q=95.34, p<0.01; I2=89.51, 95% CI: 84.61-94.42). Regression analysis indicated that the study design (retrospective vs. prospective) was associated with the heterogeneity of pooled sensitivity and specificity (all p<0.05). Conclusion: Although more prospective studies are required to validate the role of CSF LAM assay, current evidence support that the performance of CSF LAM assay is unsatisfactory for the TBM diagnosis. Additionally, optimization of the CSF LAM assay (e.g., improvements in CSF collection and preparation methods) should be considered to improve its performance.